Evaluation and comparison of six noninvasive tests for prediction of significant or advanced fibrosis in nonalcoholic fatty liver disease. Issue 8 (October 2019) - Staufer, Katharina; Halilbasic, Emina; Spindelboeck, Walter; Eilenberg, Magdalena; Prager, Gerhard; Stadlbauer, Vanessa; Posch, Andreas; Munda, Petra; Marculescu, Rodrig; Obermayer-Pietsch, Barbara; Stift, Judith; Lackner, Carolin; et al.
Background: In nonalcoholic fatty liver disease (NAFLD), advanced fibrosis has been identified as an important prognostic factor with increased liver-related mortality and treatment need. Due to the high prevalence of NAFLD, noninvasive risk stratification is needed to select patients for liver biopsy and treatment. Objective: To compare the diagnostic accuracy of several widely available noninvasive tests for assessment of fibrosis among patients with NAFLD with or without nonalcoholic steatohepatitis (NASH). Methods: We enrolled consecutive patients with NAFLD admitted to two Austrian referral centers who underwent liver biopsy. Liver stiffness measurement (LSM) was obtained by vibration-controlled transient elastography (VCTE, FibroScan) and blood samples were collected for determination of enhanced liver fibrosis (ELF) test, FibroMeter V2G, FibroMeter V3G, NAFLD fibrosis score (NFS), and fibrosis-4 index (FIB-4). Results: Our study cohort contained 186 patients with histologically confirmed NAFLD. On liver histology, NASH was present in 92 patients (50%), significant fibrosis (F ≥ 2) in 71 patients (38%), advanced fibrosis (F ≥ 3) in 49 patients (26%), and F ≥ 3 plus NASH in 35 patients (19%). For diagnosis of F ≥ 2, F ≥ 3, and F ≥ 3 plus NASH, respectively, receiver operating characteristic (ROC) analysis revealed superior diagnostic accuracy of ELF score (area under ROC curve (AUROC) 0.85, 0.90, 0.90), FibroMeter V2G (AUROC 0.86, 0.88, 0.89), FibroMeter V3G (AUROC 0.84, 0.88, 0.88), and LSM per protocol (AUROC 0.87, 0.95, 0.91) versus FIB-4 (AUROC 0.80, 0.82, 0.81) or NFS (AUROC 0.78, 0.80, 0.79). Conclusion: Proprietary fibrosis panels and VCTE show superior diagnostic accuracy for noninvasive diagnosis of fibrosis stage in NAFLD as compared to FIB-4 and NFS.